The effectiveness of an extra-curricular lecture for STI prevention and sexual education. (10th February 2023) - Reinholz, M.; Nellessen, T.; Wei, E.; Zippel, S.; Fuchs, C.; Kaemmerer, T.; Clanner-Engelshofen, B. M.; Frommherz, L. H.; Rummel, M.; French, L. E.; Stadler, P.-C.
Abstract: While the incidence of infections with the human immunodeficiency virus largely remained unchanged in Germany, an increase of other sexually transmitted infections (STIs) was observed. The aim was to analyse the effectiveness of our sexual education lecture for students in improving the awareness, knowledge and prevention of STIs. We conducted a cross-sectional survey after students had attended our extra-curricular lecture at the Department of Dermatology of the Ludwig-Maximilians-University of Munich, Germany (LMU). We compared the data with a previously performed study in which the same survey was carried out before the lecture had started. A total of 5866 questionnaires were included in the analysis. After attending the lecture significantly more students were aware of STIs (syphilis: 36.8% (before) vs. 63.5% (after); chlamydia: 30.5% vs. 49.3%; gonorrhoea: 22.4% vs. 38.2%; human papillomaviruses (HPV): 17.7% vs. 30.2%), the transmission pathways of STIs (oral: 36.6% vs. 82.6%; vaginal: 81.8% vs. 97.3%; anal: 42.8% vs. 94.0%; penile: 68.7% vs. 92.1%), knew that the HPV vaccination is directed against a virus (36.8% vs. 56.9%) and were interested in receiving a vaccination (57.7% vs. 78.8%). This study demonstrates the positive educative effects of our lecture for awareness and improved knowledge of STIs. To satisfy the need for a comprehensive sexual education, a combination of school and health facility-based programmes should be implemented as one single lecture cannot convey the entire information about STIs.